A new species of Microdeutopus, M. periergos sp. nov. (Crustacea, Amphipoda, Senticaudata, Aoridae) from Cyprus (East Mediterranean Sea) - Myers, Alan; Plaiti, Wanda; Rousou, Maria (Zootaxa, 2018)
A new species of Microdeutopus, M. periergos sp. nov. is described from Cyprus. This brings the total number of species of Microdeutopus known from the Mediterranean Sea to twelve. It is described and figured here and a key to the genus is provided.